2018
DOI: 10.1002/jper.16-0752
|View full text |Cite
|
Sign up to set email alerts
|

Chronic periodontitis and oral health‐related quality of life in Chinese adults: A population‐based, cross‐sectional study

Abstract: Chronic periodontitis was associated with poorer OHRQoL in Chinese adults. In addition, the impairment in OHRQoL showed a significant correlation with the severity of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
32
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 41 publications
9
32
2
2
Order By: Relevance
“…The results of this study showed that the combined occurrence of dental caries and periodontitis is associated with a negative impact on the oral health-related quality of life. Previous studies have generally analyzed only one of these oral conditions, 6,8,13,[15][16][17] and to our best knowledge, the present investigation is the first to evaluate the coexisting effect of caries and periodontitis, as well as employing a control group without either disease.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of this study showed that the combined occurrence of dental caries and periodontitis is associated with a negative impact on the oral health-related quality of life. Previous studies have generally analyzed only one of these oral conditions, 6,8,13,[15][16][17] and to our best knowledge, the present investigation is the first to evaluate the coexisting effect of caries and periodontitis, as well as employing a control group without either disease.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to investigations in other countries and regions that evaluated the impact of these oral conditions on quality of life separately. 8,[13][14][15][16][17]36 In these studies, individuals with severe periodontitis reported a greater negative impact on quality of life related to oral health. 8,13,15,17 So too with dental caries, in that the greater its severity, the greater the impact perception.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations